2009
DOI: 10.1055/s-0028-1103293
|View full text |Cite
|
Sign up to set email alerts
|

Drug Prescription Patterns in Schizophrenia Outpatients: Analysis of Data from a German Health Insurance Fund

Abstract: At 60%, the proportion of patients in this study treated with atypical antipsychotics was surprisingly high. Of significant interest is the frequent prescription of clozapine (14%). The results are discussed in comparison to comparable studies from other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 21 publications
7
26
0
1
Order By: Relevance
“…The rates of clozapine prescription for TRS patients found in Brazilian community centers were similar to rates found in studies carried out in the United States 28,29 , an especially low proportion when compared to other countries 26,27,30 . Clozapine was only prescribed for 22 individuals, which represents 21.4% of the TRS patients, or 5% of the total number of schizophrenia patients, despite the abundant evidence of clozapine's superior efficacy and effectiveness compared with other antipsychotic drugs in the treatment of TRS patients 6,7,8,13,31,32 .…”
Section: Discussionsupporting
confidence: 64%
“…The rates of clozapine prescription for TRS patients found in Brazilian community centers were similar to rates found in studies carried out in the United States 28,29 , an especially low proportion when compared to other countries 26,27,30 . Clozapine was only prescribed for 22 individuals, which represents 21.4% of the TRS patients, or 5% of the total number of schizophrenia patients, despite the abundant evidence of clozapine's superior efficacy and effectiveness compared with other antipsychotic drugs in the treatment of TRS patients 6,7,8,13,31,32 .…”
Section: Discussionsupporting
confidence: 64%
“…The most preferred antipsychotic combination was quetiapine plus risperidone [12]. In Germany, it was olanzapine [45] and in Korea, it was risperidone and haloperidol but the monotherapy group was olanzapine. In the UK (2007–2011), the primary care setting most commonly prescribed first- and second-generation antipsychotics: olanzapine, risperidone and chlorpromazine, respectively [46].…”
Section: Discussionmentioning
confidence: 99%
“…While similar studies show that the prevalence of the above mentioned adverse effects was low in patients on fluphenazine and haloperidol. 27,1,29 This difference could be due to the clinician's preferential use of these drugs in patients subsequent to the development of obesity and/or diabetes mellitus following the use of atypical agents.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several publications have indicated that atypical antipsychotic drugs are superior in efficacy to conventional antipsychotic drugs especially with respect to control of negative symptoms and lack of extrapyramidal side effects, these being the limiting factors with the conventional drugs. 2 A study on metabolic syndrome in outpatients receiving antipsychotic therapy by Mainara AS et al has shown that prevalence of metabolic syndrome was significantly higher in subjects on antipsychotics (27.0%) and elevated body mass index was seen in 33.40% of them.…”
Section: Introductionmentioning
confidence: 99%